Procalcitonin in the Post-Operative Burn Patient - Ludo Masole; Chikwendu J. Ede; Adelin Muganza (MDPI AG, 2023)
Serum procalcitonin (PCT) is a biomarker used to diagnose sepsis and infection. Following invasive bacterial infection, PCT is detectable in peripheral blood. The aim of our study was to determine if there is a relationship between serum PCT post-burn wound debridement and burn-related sepsis. In total, 34 participants were recruited from 1 November 2019 to 31 July 2020. Serum PCT levels were drawn on days 0, 1, 2, and 3, with day 0 being the day of the surgery. Blood culture samples were drawn on days 0 and 3. Statistical analyses were performed using STATA©. Descriptive statistics were presented as the median for continuous data and frequencies for categorical data. A two-sample Wilcoxon-Mann-Whitney test was performed to assess the correlation between the PCT values and blood culture positivity. In all, 33 burn debridement procedures were completed, and 1 patient demised before surgery. The median age was 35.5 years; 61.8% were male. Four patients had comorbidities. There was a trend of higher PCT values from day 0 to day 3. The median PCT on day 0 was 3.30 µg/L (IQR 0.78-15.10), compared to day 3 PCT which was 5.15 µg/L (IQR 1.35-18.55). The median values for serum PCT for days 0 to 3 were above the normal threshold regardless of BC positivity. There was a statistically significant difference in the PCT levels between positive and negative BC, with a p value of 0.0087 for day 3 serum PCT. The findings indicate an association of a high serum PCT level with a positive blood culture in a burn patient post-debridement surgery. A higher numerical threshold/cut-off of serum PCT should be used for this cohort of patients, to aid in the diagnosis of sepsis. A cut-off value could not be determined due to the small sample size.